Dynamic tensile mechanical properties and failure mode of zirconium diboride‐silicon carbide ceramic composites. Issue 3 (9th January 2020) - Liu, Jianhao; Hu, Zhou; Zhang, Yuxia
Abstract: Dynamic indirect tension experiments were performed on zirconium diboride‐silicon carbide (ZrB2 −20%SiC) ceramic. Flattened Brazilian disc specimens of ZrB2 −20%SiC were prepared to conduct dynamic tensile tests using the modified Split Hopkinson pressure bar system. The tensile experiments were completed at the range of loading rates from 7.53 to 74.71 GP s −1 . The tensile experimental results revealed that the zirconium diboride‐silicon carbide ceramic composite is rate‐sensitive in terms of the tensile strength and failure mode. The dynamic tensile strength increases linearly with the loading rate and changes from 195 MPa at 7.53 GP s −1 to 654 MPa at 74.71 GP s −1 . Moreover, the dynamic tensile strength decreases with the increase in critical fracture time, which conforms to Tuler and Butcher's fracture criterion. In dynamic experiments, a high‐speed camera was used to examine the tensile failure process, and fragments were collected to analyze the dynamic tensile failure mechanism. The tensile fracture mode of ZrB2 −20%SiC obviously showed the sensitivity of the loading rate. The fragment size of ZrB2 −20%SiC ceramic decreased but the quantity of fragments increased as the loading rate increased.